Information Technology, Dynamic Capabilities, and Strategic Planning in the Oil and Gas Supply Chain - Eduard Sinaga; Adrid Indaryanto; Bambang Dwi Harijadi (Logistic and Operation Management Research (LOMR), 2024)
Uncertainties, including the COVID-19 epidemic, and variations in demand affect the oil and gas sector. Owing to the reliance on various suppliers, oil and gas projects require effective supply chain management. Ineffective management can result in overspending, delays, and legal issues. This study examined how supply chain management is affected by changes in the sector. This study investigated the connections between information technology, strategic planning, dynamic management competencies, and managerial performance in oil and gas projects. Purposive sampling was used in the study, with managers or heads of supply chain departments as the target audience. Partial least squares structural equation modeling (PLS-SEM) was used to evaluate the data obtained from an online survey and test the proposed correlations between the research variables. The findings demonstrated that management performance was positively impacted by strategic planning and information technology through the increased dynamic capacities of managers. This study contributes by combining information technology, strategic planning, and dynamic capabilities into a unified model. Results shed light on how supply chain management is impacted by changes in the sector. Useful recommendations are provided for businesses looking to enhance supply chain performance despite difficulties.